Pengembangan Sistem Pendukung Keputusan untuk Pemilihan Karyawan Terbaik di PT. Bringin Karya Sejahtera Cabang Ragunan, Jakarta Selatan, Menggunakan Metode Analytical Hierarchy Process (AHP) Berbasis Web - Warahmah, Mawadah; Faizah, NM; Nurcahyo, Widyat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research develops a decision support system using the Analytical Hierarchy Process (AHP) to assist in selecting the best employee at PT. Bringin Karya Sejahtera. Evaluating employee performance is crucial for enhancing company productivity, as recognizing outstanding performance can motivate employees to excel. This case study was conducted at PT. Bringin Karya Sejahtera, where employee evaluations are carried out monthly, with cumulative results calculated at the end of the year to determine the best employee. The selection process often becomes complex due to the numerous criteria and employee options, requiring a system to simplify decision-making. Therefore, this study introduces an AHP-based system to support leaders in effectively managing factors, criteria, and alternatives. AHP, developed by Thomas L. Saaty, allows for multi-criteria comparisons and simplifies complex decision-making through a hierarchical approach.